STUDI KUALITAS AIR TANAH DANGKAL UNTUK KONSUMSI BERDASARKAN SATUAN LITOLOGI DI KANAGARIAN DESA BARU KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - -, Sukini - (Pendidikan Geografi, 2014)
The background of this reseach is in the area of public complaints research using shallow ground water which they do not meet the standards. This research aims to obtain data informations and discuss data on the quality of shallow groundwater based on lithologic unit for drinking water in the village of Desa Baru District Ranah Batahan District Pasaman covering physics requirements (temperature, color, odor, taste, turbidity, dissolved solids ), terms of chemical properties (pH, Fe, hardness, nitrate) and biological (E-Coli). The Research is descriptive method that describe and explain something, methods and techniques of the Research include acquiring, processing and analysis of data, both primary data and secondary. Based on observations in the field and laboratory, showed that shallow ground water quality based lithological units in the research area have adapted to the Drinking Water Quality Standards of Decree of the Minister of Health No. 429 / Menkes / Per / IV / 2010. Results In the Reseach rocks Jorong Mulyorejo Qta in terms of physical (smell and taste) and chemical (Fe) 3.638 laboratory test results in terms of the biology of bacteria (E-Coli) laboratory test results of 240 / 100 ml does not meet the standards. In Tmv unit in Jorong Sidomulyo physically (color, smell, taste, and turbidity), laboratory test results 54 TCU color, turbidity 41.0 NTU in terms of chemistry (Fe) 2.320 Mg results of laboratory tests / L and in terms of bacterial Biology (E-Coli) laboratory test results of 9 / 100ml does not meet the standards. On the litology unit of Tvmt in Jorong Karangrejo physically (temperature, color, odor, taste, turbidity, and TDS) has met the standard, in terms of chemistry (Fe) 0.663 Mg results of laboratory tests / L in terms of the biology of bacteria (E-Coli) results laboratory test 93 / 100ml does not meet drinking water quality standards.